HPV‐negative high‐grade cervical precancerous lesions or invasive cancer in China: A post hoc analysis of a multicentric clinical study. Issue 1 (8th December 2022) - Bao, Heling; Zhao, Yun; Zhang, Xiaosong; Bi, Hui; Cong, Shu; Fang, Liwen; Wang, Hai‐Jun; Wang, Linhong
Abstract: Objective: To evaluate HPV‐negative cervical high‐grade precancerous lesions or cancer in China. Methods: Histologically confirmed cervical intraepithelial neoplasia grade 2 or worse (CIN2+) were searched in a multicentric clinical study. All patients underwent cobas HPV testing, liquid‐based cytology, DNA ploidy analysis, and colposcopy‐guided biopsy. According to clinical practice, patients underwent p16 ink4a staining and cone biopsy. Comparisons were made between HPV‐negative and ‐positive patients for clinical characteristics. Results: The study found 61 cases of cobas HPV‐negative CIN2+ among 797 cases of histologically confirmed CIN2+, including 38 CIN2, 20 CIN3, and 3 invasive cancers. The prevalence of HPV‐negative CIN2+ and CIN3+ was 7.7% (95% confidence interval [CI] 5.8–9.5) and 5.7% (95% CI 3.5–8.0), respectively. Among 24 cases with p16 staining, 20 showed p16 positivity. The proportions of normal or minor abnormalities in terms of colposcopy, cytology, and DNA ploidy were higher in HPV‐negative cases than in HPV‐positive cases. When adding cytology to the screening of symptomatic or previously HPV‐positive women, the prevalence of HPV‐negative CIN2+ or CIN3 would decrease by approximately 50%. Conclusion: Less than one‐tenth of CIN2+ are missed by HPV‐only screening, and they have smaller lesions than HPV‐positive cases. Colposcopy should be considered for symptomatic or previously HPV‐positive women with HPV‐negative results. Synopsis: Less than one‐tenth of CIN2+ are missed by HPV‐only screening in China, and colposcopy should be considered for women who are symptomatic but negative for HPV.